PENERAPAN AROMA TERAPI LEMON TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI SECTIO CAESAREA - Dwi Kristianto, Antonius; Hastuti, Witri (NHM PRESS, 2023)
Anxiety is one of the problems commonly experienced by mothers before SC surgery. If this anxiety is not addressed, it can have negative impacts such as increased blood pressure which can lead to the risk of bleeding during surgery. This study aims to determine the application of lemon aroma therapy to the anxiety level of pre-SC surgery patients. This research is a case study, where the research subjects were two pre-SC surgery mothers who experienced moderate anxiety who were given aromatherapy for 15 minutes. Measurement of anxiety levels was carried out before and after giving the intervention. The results of the study showed that providing aromatherapy was effective in reducing maternal anxiety levels before SC surgery.